Implementasi Aksi Clean Up untuk Meningkatkan Kesadaran dan Kebersihan Lingkungan Pesisir di Desa Watorumbe, Kabupaten Buton Tengah - muhammad alwi, alwi; Ode Abdul Gamsir, La; Muliati, Eka; Zumar Timboubo, Muh.; Nur Andini, Vika; Fitria Mukti, Elisa; Fiqih, Muhamad; Arman, Arman; Salman, Salman; Hidayat, Rian; Rahman Malsina, Abdul; Sayia, Sayia; Rafiah, Siti; Lisna, Wa; Niati, Wa (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
The coastal clean-up activity in Watorumbe Village, Central Mawasangka District, Central Buton Regency, aimed to reduce waste pollution in coastal areas while increasing community awareness of environmental cleanliness. The program was conducted on August 10, 2025, involving students, environmental communities, and local residents. The methods included preparation, implementation, and waste collection and disposal to the final landfill. The results indicated active participation of around 60 people, collecting approximately ten large garbage bags of plastic and organic waste. Positive impacts included improved coastal cleanliness, reduced health risks caused by waste, and strengthened community cooperation and environmental concern. However, challenges such as limited waste management facilities and low awareness among some residents remain. Therefore, regular clean-up programs, adequate supporting facilities, and continuous environmental education are recommended to maintain coastal cleanliness sustainably.